Measuring the effects of listening for leisure on outcome after stroke (MELLO): A pilot randomized controlled trial of mindful music listening. Issue 2 (February 2020) - Baylan, Satu; Haig, Caroline; MacDonald, Maxine; Stiles, Ciara; Easto, Jake; Thomson, Meigan; Cullen, Breda; Quinn, Terence J; Stott, David; Mercer, Stewart W; Broomfield, Niall M; Murray, Heather; et al.
Background: Cognitive deficits and low mood are common post-stroke. Music listening is suggested to have beneficial effects on cognition, while mindfulness may improve mood. Combining these approaches may enhance cognitive recovery and improve mood early post-stroke. Aims: To assess the feasibility and acceptability of a novel mindful music listening intervention. Methods: A parallel group randomized controlled feasibility trial with ischemic stroke patients, comparing three groups; mindful music listening, music listening and audiobook listening (control group), eight weeks intervention. Feasibility was measured using adherence to protocol and questionnaires. Cognition (including measures of verbal memory and attention) and mood (Hospital Anxiety and Depression Scale) were assessed at baseline, end of intervention and at six-months post-stroke. Results: Seventy-two participants were randomized to mindful music listening ( n  = 23), music listening ( n  = 24), or audiobook listening ( n  = 25). Feasibility and acceptability measures were encouraging: 94% fully consistent with protocol; 68.1% completing ≥6/8 treatment visits; 80–107% listening adherence; 83% retention to six-month endpoint. Treatment effect sizes for cognition at six month follow-up ranged from d = 0.00 ([−0.64, 0.64], music alone), d = 0.31, ([0.36, 0.97], mindful music) for list learning; to d = 0.58 ([0.06, 1.11], music alone), d = 0.51 ([−0.07, 1.09], mindful music) for immediate story recall; and d = 0.67 ([0.12, 1.22], music alone), d = 0.77 ([0.16, 1.38]mindful music) for attentional switching compared to audiobooks. No signal of change was seen for mood. A definitive study would require 306 participants to detect a clinically substantial difference in improvement (z-score difference = 0.66, p  = 0.017, 80% power) in verbal memory (delayed story recall). Conclusions: Mindful music listening is feasible and acceptable post-stroke. Music listening interventions appear to be a promising approach to improving recovery from stroke.